지속 가능한 농업생산성 증대를 위한 질소 이용 효율 향상 - 장안철(Ancheol Chang); 최지영(Ji-Young Choi); 박순기(Soon-Ki Park); 김동헌(Dong-Hern Kim); 배신철(Shin-Chul Bae) (Korean journal of breeding, 2011)
Agriculture plays a vital role in the sustenance of human society and is the fundamental of developing economies. Nitrogen is one of the most critical inputs that define crop productivity. To ensure better value for investment as well as to minimize the adverse impacts of the accumulative nitrogen species in environment, improving nitrogen use efficiency of crop plants is of key importance. Efforts have been made to study the genetic and molecular biological basis as well as the biochemical mechanisms involved in nitrogen uptake, assimilation, translocation and remobilization in crops and model plants. This review gives an overview of metabolic, enzymatic, genetic and biotechnological aspects of nitrogen uptake, assimilation, remobilization and regulation. This review presents the complexity of nitrogen use efficiency and the need for an integrated approach combining physiology, quantitative trait genetics, system biology, soil science, ecophysiology and biotechnological interventions to improve nitrogen use efficiency.